The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s13046-021-02066-7
|View full text |Cite
|
Sign up to set email alerts
|

The non-canonical mechanism of ER stress-mediated progression of prostate cancer

Abstract: Background The development of persistent endoplasmic reticulum (ER) stress is one of the cornerstones of prostate carcinogenesis; however, the mechanism is missing. Also, alcohol is a physiological ER stress inducer, and the link between alcoholism and progression of prostate cancer (PCa) is well documented but not well characterized. According to the canonical model, the mediator of ER stress, ATF6, is cleaved sequentially in the Golgi by S1P and S2P proteases; thereafter, the genes responsibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…The segregation of S1P and S2P from Golgi and activation of ATF6 are positively correlated with AR signaling, different disease stages, and alcohol consumption. Significantly, the depletion of ATF6 retarded the growth of xenograft prostate tumors and blocked the production of pro-metastatic metabolites [220]. Another important observation from our study is that in PCa patients consuming alcohol, cribriform patterns in the tumor area (a clinically significant prognostic indicator for advanced PCa) were larger than in non-alcoholic patients.…”
Section: The Cellular Mechanisms Of Alcohol's Effect On the Progressi...mentioning
confidence: 47%
See 1 more Smart Citation
“…The segregation of S1P and S2P from Golgi and activation of ATF6 are positively correlated with AR signaling, different disease stages, and alcohol consumption. Significantly, the depletion of ATF6 retarded the growth of xenograft prostate tumors and blocked the production of pro-metastatic metabolites [220]. Another important observation from our study is that in PCa patients consuming alcohol, cribriform patterns in the tumor area (a clinically significant prognostic indicator for advanced PCa) were larger than in non-alcoholic patients.…”
Section: The Cellular Mechanisms Of Alcohol's Effect On the Progressi...mentioning
confidence: 47%
“…glass of wine-1 or more times per day; 3.4 oz. of strong liquor at least once per day) [220]. We found that alcohol-induced Golgi disorganization was associated with monomerization of trans-golgin, GCC185, the Golgi retention partner of S1P and S2P.…”
Section: The Cellular Mechanisms Of Alcohol's Effect On the Progressi...mentioning
confidence: 79%
“…As a result, several ER stress response element genes such as GRP78, GRP94, CHOP can be activated, and promote the ER associated protein degradation gene XBP1 (X-box binding protein 1) transcription. The ATF6f can bind XBP1 and control the expression of some specific genes ( Zhang et al, 2019b ; Pachikov et al, 2021 ).…”
Section: Reactive Oxygen Species and Endoplasmic Reticulum Stressmentioning
confidence: 99%
“…The mechanisms involved in regulating cell apoptosis under the conditions of irreversible ER stress are now partially understood, and multiple pathways are involved in ER-mediated cell apoptosis [ 8 ]. PERK and IRE1 are type-I transmembrane proteins, which could act on their downstream targets after phosphorylation, while type II transmembrane kinase ATF6 needs to be spliced by site 1 protease (S1P) and site 2 protease (S2P) in the Golgi apparatus before translocating into the nucleus to induce the transcription of its downstream target [ 10 ]. All three targets can promote apoptosis by activating the transcription of the growth arrest and DNA damage-inducible protein 34 (GADD34) and C/EBP homologous protein (CHOP), which are essential for cell apoptosis.…”
Section: Er Stress and Cell Fatementioning
confidence: 99%